Macroeconomic Determinants of Labour Productivity: An Empirical Analysis of The Republic of North Macedonia - Kozheski, Kristijan; Slaveski, Trajko; Trpeski, Predrag; Trenovski, Borche (My University, 2024)
This study examines the determinants of labour productivity in the Republic of North Macedonia, with a particular emphasis on key macroeconomic variables such as gross investment, employment, workers' compensation, inflation, gross national income per capita, and human capital. Labour productivity is recognized as a pivotal indicator of labour market efficiency, and worker welfare, and a crucial driver of sustainable economic growth. Despite improvements in employment levels and reductions in unemployment, labour productivity in North Macedonia remains suboptimal, exhibiting stagnation and insufficient growth, especially when contrasted with increasing wages. Through the application of both correlation and regression analyses, this paper explores the strength and causal relationships between labour productivity and macroeconomic variables, highlighting their role in shaping national competitiveness and economic development. The findings align with both theoretical and empirical literature, reinforcing the significance of human capital, gross investment, and overall economic performance in driving productivity improvements. This study contributes to the discourse on structural challenges within North Macedonia's labour market and provides a basis for policy interventions aimed at fostering sustainable productivity growth and enhancing international competitiveness.
Keywords: Labour market; Productivity of labour; Determinants